Dynamic Records Management in the General Section of the PD Office Makassar Raya Parking - Muh. Darwis; Putri Ekawati Yusup; Sitti Hardiyanti Arhas (International Journal of Administration and Education (IJAE), 2024)
The office is a place to carry out administrative activities to achieve predetermined goals. This research is a qualitative descriptive study that aims to determine Dynamic Records Management in the General Section of the PD office Makassar Raya Parking. The number of informants in this research was 5 people, namely, Head of General Affairs, Kasie. Admin/Clerk and 3 General Staff. The data collection techniques used were observation, interviews, and documentation methods. The data analysis techniques used are data reduction, data presentation, conclusions, and verification. The research results show dynamic archive management in the General section of the PD office Makassar Raya parking in the flow of creating and receiving archives is carried out well, the process of distributing letters to office units is correct, the process of borrowing archives using dynamic archives is still not good because clear borrowing rules have not been implemented and depreciation of dynamic archives is carried out by moving and destroying archives. This research can be used as material for knowledge about dynamic archive management in more depth, where this research uses qualitative methods that produce a more detailed description, based on the results of research on dynamic archive management in the flow of creating and receiving letters, there are differences due to differences in the urgency of letters.